Mesenteric thrombosis as a clinical presentation of antiphospholipid syndrome: a case report and literature review - Dzul, Jose E.; Sonda, Valeria G.; Carrillo, Carolina; Segura, Vanesa Lopez (International Journal of Research in Medical Sciences, 2024)
Mesenteric thrombosis is a rare pathology that results from the obstruction of the arterial or venous system of the mesenteric circulation by a thrombus or embolus. The etiology of thrombus formation is rarely evident; the population statistically most affected by this pathology are older adults, with an average age of 60-70 years. The main causes related to the presentation of mesenteric thrombosis are embolic cardiac arrhythmias such as atrial fibrillation, neoplasia and prolonged prostration. In rare cases, the presence of thrombophilia, for example antiphospholipid antibody syndrome (APS), is identified as an underlying cause of thrombotic events. APS is a disease characterized by a procoagulant state; the most frequent clinical manifestations are related to thrombotic events. The pathophysiology of the disease is related to the formation of antiphospholipid antibodies. The three antibodies identified in APS are lupus anticoagulant (LA), anticardiolipin antibody (aCL) and anti-b2glycoprotein 1 antibody (anti-b2GP1). Treatment is based on the use of anticoagulant drugs with the aim of preventing the appearance of new thromboembolic events. In this article we present a clinical case of mesenteric thrombosis in a male patient in whom the presence of antiphospholipid antibodies (aPL) was documented and who met the classification criteria for APS. For the review of the literature, a search was carried out for information related to pathophysiology, clinical manifestations, classification and treatment of APS, as well as literature related to mesenteric thrombosis in open access sources and databases such as PubMed. In conclusion, APS is a rare pathology, probably because it is underdiagnosed, since in developing countries there are no resources to carry out the diagnostic approach, likewise the delay in the start of treatment implies an increase in morbidity for the patient.